Stingless bee (Tetragonula carbonaria) foragers prioritise resin and reduce pollen foraging after hive splitting - Newis, Ryan; Nichols, Joel; Farrar, Michael B.; Fuller, Chris; Hosseini Bai, Shahla; Wilson, Rachele S.; Wallace, Helen M. (Apidologie, 2023)
Stingless bees are increasingly in demand as pollinators in agricultural crops within the tropics and subtropics. Hive splitting, where one strong managed hive is “split” into two independent daughter colonies, is commonly used to increase hive numbers. However, how splitting impacts foraging behaviour or the time taken for the colony to recover from splitting has not previously been studied. We assessed the impact of splitting on the foraging behaviour of Tetragonula carbonaria colonies. The number of returning forager trips and foraged proportions of pollen, nectar and resin was observed after splitting and compared with unsplit control hives over a 31-day period. We found the total amount of returning foragers in split hives reduced to less than a third of unsplit hives (unsplit median, 184–288; split median, 19–61) for 16 days, while returning nectar (unsplit median, 89–147; split median, 16–28) and pollen (unsplit median, 55–155; split median, 1–7) foragers reduced to less than a quarter of unsplit hives for 9 days following splitting. After 31 days, the number of total, nectar and pollen foraging trips had still not recovered to levels observed in unsplit hives. Resin foraging trips however were not significantly different to unsplit hives after only 10 days. The colony foraging allocation to resin (proportion) increased after splitting and was significantly higher in split hives until day 16 of the experiment (unsplit median, 0.03–0.05; split median, 0.10–0.16). Our results demonstrate that split colonies prioritise resin collection and foraging on floral resources is reduced. We recommend that hives should not be split within 31 days of being used for pollination, and resin sources should be conserved where possible and supplemented where necessary due the vital roles of the resource.